15 CARPENTER'S SYNDROME: DISCUSSION OF LONG-TERM FOLLOW-UP. Issue 1 (1st January 2007) - Huang, P.; Bay, C.; Vasconez, H.; Cottrill, C.
Abstract : Carpenter's syndrome is a rare autosomal recessive disease that belongs to a group of craniosynostosis syndromes. As the name of the group of syndromes implies, these spatients have early fusion of the cranial sutures or abnormal growth of the cranial vault. In either of these events, the small cranial vault does not allow the brain to grow properly. These children usually have surgery between the ages of 8 and 10 months. It is very rare for children not to have surgery. The surgery not only gives improvement for cosmetic appearances but allows for the brain to grow appropriately. We will present an overview of Carpenter's syndrome as well as other syndromes belonging to this group. We will explain the genetic component to these syndromes and present an untreated patient in her twenties who now has several residual problems.